Transformasi Digital dan Sistem Informasi Manajemen: Inovasi untuk Keberhasilan Bisnis Wirausaha - Wahyudin, Ade; Iskandar, Didik; Aprianto, Muhammad Rafli; Karimi, Salman Izudin (Syntax Corporation, 2025)
Digital transformation has become a key factor in enhancing the efficiency and competitiveness of entrepreneurial businesses. By implementing management information systems (MIS), entrepreneurs can optimize data-driven decision-making and manage resources more effectively. This study analyzes the role of digital transformation and innovation in MIS on business success, as well as the challenges faced in its implementation. The findings indicate that adopting digital technology improves operational efficiency, expands market access, and drives product and service innovation. However, budget constraints, lack of skilled human resources, and resistance to change remain major obstacles. Therefore, effective strategies are needed to overcome these challenges and maximize the benefits of digital transformation in entrepreneurial businesses.